2014
DOI: 10.1002/acr.22264
|View full text |Cite
|
Sign up to set email alerts
|

Primary Sjögren's Syndrome: Diagnostic and Prognostic Value of Salivary Gland Ultrasonography Using a Simplified Scoring System

Abstract: Objective. To determine the usefulness and prognostic value of a simplified salivary gland ultrasonography (SGUS) scoring system in primary Sjögren's syndrome (SS). Methods. Patients with primary SS (n ‫؍‬ 105) and controls (n ‫؍‬ 57) were evaluated using a simplified SGUS scoring system. Parenchymal homogeneity in salivary glands was graded from 0 to 3, with grades 0 (normal) and 1 (mild inhomogeneity) being interpreted as normal or unspecific, and grades 2 (several rounded) and 3 (numerous or confluent hypoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
130
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(147 citation statements)
references
References 17 publications
14
130
1
2
Order By: Relevance
“…We agree that the visualization of parenchymatous inhomogeneity, with sensitivity of 74 % and specificity of 53 %, is a useful tool in the diagnostic setup. The lack of standardized examination protocols and the high reliance on personal physician expertise are expressed in a wide range of measured specificities (73-99 %) and sensitivities (59-94 %), which prevent reliable data acquisition, and therefore preclude comprehensive clinical application [32][33][34][35][36][37]. In concordance with recent studies, we demonstrated good intra-and inter observer reliability for ARFI imaging [38][39][40].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We agree that the visualization of parenchymatous inhomogeneity, with sensitivity of 74 % and specificity of 53 %, is a useful tool in the diagnostic setup. The lack of standardized examination protocols and the high reliance on personal physician expertise are expressed in a wide range of measured specificities (73-99 %) and sensitivities (59-94 %), which prevent reliable data acquisition, and therefore preclude comprehensive clinical application [32][33][34][35][36][37]. In concordance with recent studies, we demonstrated good intra-and inter observer reliability for ARFI imaging [38][39][40].…”
Section: Discussionsupporting
confidence: 84%
“…High-resolution B-mode ultrasound has been suggested as a non-invasive technique in the assessment of pSS. Different scoring systems have been introduced that assess parenchymatous homogeneity, echogenicity, size of the glands, and posterior glandular border [26,[32][33][34][35][36][37]. We agree that the visualization of parenchymatous inhomogeneity, with sensitivity of 74 % and specificity of 53 %, is a useful tool in the diagnostic setup.…”
Section: Discussionmentioning
confidence: 87%
“…In the Hocevar scoring system, homogeneity and hypoechogenic areas are scored separately. On the other hand, in the scoring system used by Theander and Mandl,12 only parenchymal homogeneity is measured. However, when taking a closer look at their scoring system, in fact a combination of homogeneity and hypoechogenic areas is scored 12.…”
Section: Discussionmentioning
confidence: 99%
“…On ultrasound imaging, she also had discrete hypoechoic foci occupying more than 50% of her parotid and submandibular glands, changes that are commonly seen in Sjögren's syndrome. 14 One patient had a pre-existing history of severe dry eye disease, but no diagnosis of Sjögren's syndrome and no severe dry mouth symptoms. Two of the patients with sicca syndrome developed other IRAEs; pneumonitis developed in one patient and interstitial nephritis and colitis in the other.…”
Section: Sicca Syndromementioning
confidence: 99%